2022
DOI: 10.1038/s41375-022-01662-6
|View full text |Cite
|
Sign up to set email alerts
|

An immunity and pyroptosis gene-pair signature predicts overall survival in acute myeloid leukemia

Abstract: Treatment responses of patients with acute myeloid leukemia (AML) are known to be heterogeneous, posing challenges for risk scoring and treatment stratification. In this retrospective multi-cohort study, we investigated whether combining pyroptosis- and immune-related genes improves prognostic classification of AML patients. Using a robust gene pairing approach, which effectively eliminates batch effects across heterogeneous patient cohorts and transcriptomic data, we developed an immunity and pyroptosis-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Besides risk score, molecular risk and age were shown to be independent risk factors for OS and then were enrolled to multivariate Cox regression ( Figure 5A ). The risk score demonstrated a higher predictive ability than that of clinicopathological variables in AML ( Figure 5B ) and other previously reported prognostic signatures [Leu 2022 ( Kong et al, 2022 ), AJH 2021 ( Chen et al, 2021 ), Int Imp 2022 ( Shao et al, 2022 )] (iAUC-Our signature: 0.806, iAUC-Leu2022: 0.691, iAUC-AJH2021: 0.570, and iAUC-IntImp2022: 0.658; all the p -values in comparisons between Our signature and the above three models were <0.001). Based on multivariate Cox regression, we developed a novel nomogram, aiming to optimize the predictive accuracy of the risk model ( Figure 5D ).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Besides risk score, molecular risk and age were shown to be independent risk factors for OS and then were enrolled to multivariate Cox regression ( Figure 5A ). The risk score demonstrated a higher predictive ability than that of clinicopathological variables in AML ( Figure 5B ) and other previously reported prognostic signatures [Leu 2022 ( Kong et al, 2022 ), AJH 2021 ( Chen et al, 2021 ), Int Imp 2022 ( Shao et al, 2022 )] (iAUC-Our signature: 0.806, iAUC-Leu2022: 0.691, iAUC-AJH2021: 0.570, and iAUC-IntImp2022: 0.658; all the p -values in comparisons between Our signature and the above three models were <0.001). Based on multivariate Cox regression, we developed a novel nomogram, aiming to optimize the predictive accuracy of the risk model ( Figure 5D ).…”
Section: Resultssupporting
confidence: 82%
“…Irreversible pyroptotic cell death may be caused by the activation of inflammasome in HSCs and thus leading to the origin of hematopoietic malignancies ( Wei et al, 2022 ). An immunity and pyroptosis gene-pair signature performed stronger survival predictive efficacy than 10 existing signatures ( Kong et al, 2022 ). The researches for the relationship between pyroptosis and tumor may provide some inspirations for clinical treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, we identified 52 PRGs. [25][26][27] Wilcox tests were used to assess the expression differences of PRGs between normal soft tissue and STS, and P < .05 was used as the screening criterion. Using the package "ConsensusClusterPlus," we carried out the cluster analysis based on 52 PRGs expressions in STS patients.…”
Section: Unsupervised Clustering Of Prgsmentioning
confidence: 99%
“…Pyroptosis is mainly mediated by inflammasomes and the activation of caspase family members including caspase-1, which leads to splicing and polymerization of multifarious Gasdermin family members such as GSDMD, contributing to cell perforation and then cell death [ 32 ]. Its activation mechanisms mainly include canonical, noncanonical inflammasome pathways and others.…”
Section: Molecular Mechanisms Of Pyroptosismentioning
confidence: 99%